The Pitfalls of in vivo Cardiac Physiology in Genetically Modified Mice – Lessons Learnt the Hard Way in the Creatine Kinase System - Lygate, Craig A. (Frontiers in Physiology, 2021)
In order to fully understand gene function, at some point it is necessary to study the effects in an intact organism. The creation of the first knockout mouse in the late 1980’s gave rise to a revolution in the field of integrative physiology that continues to this day. There are many complex choices when selecting a strategy for genetic modification, some of which will be touched on in this review, but the principal focus is to highlight the potential problems and pitfalls arising from the interpretation of in vivo cardiac phenotypes. As an exemplar, we will scrutinize the field of cardiac energetics and the attempts to understand the role of the creatine kinase energy buffering and transport system in the intact organism. This story highlights the confounding effects of genetic background, sex and age, as well as the difficulties in interpreting knockout models in light of promiscuous proteins and metabolic redundancy. It will consider the dose-dependent effects and unintended consequences of transgene overexpression, and the need for experimental rigour in the context of in vivo phenotyping techniques. It is intended that this review will not only bring clarity to the field of cardiac energetics, but also aid the non-expert in evaluating and critically assessing data arising from in vivo genetic modification.